2018
DOI: 10.29333/ejmste/91245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Application of Computer Multimedia Teaching to Automobile Vocational Education on Students’ Learning Satisfaction and Learning Outcome

Abstract: Along with the change in computer technology, the application of multimedia assisted teaching to education and research plays a critical role with the popularity of computer technology and the diverse development. Multimedia assisted teaching materials could assist teachers in teaching as well as enhance students' autonomous learning that computer multimedia teaching has become an alternative teaching tool beyond traditional learning. With quasi-experimental study, 216 students in the automobile applied techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Demand Analysis. Using software to analyze the collected questionnaire data, the results show that the students believe that there are some drawbacks in the traditional teaching method; they are eager to try a new teaching mode and have considerable demands on the teaching system, as shown in Table 1 and Figure 2 [12]. The dissemination and use of the system require a certain environment and background, so the future application of the system is based on the results of the questionnaire and the software is used to evaluate the feasibility of the data.…”
Section: Content Organization Structure Methods Commonly Used In Mult...mentioning
confidence: 99%
“…Demand Analysis. Using software to analyze the collected questionnaire data, the results show that the students believe that there are some drawbacks in the traditional teaching method; they are eager to try a new teaching mode and have considerable demands on the teaching system, as shown in Table 1 and Figure 2 [12]. The dissemination and use of the system require a certain environment and background, so the future application of the system is based on the results of the questionnaire and the software is used to evaluate the feasibility of the data.…”
Section: Content Organization Structure Methods Commonly Used In Mult...mentioning
confidence: 99%
“…According to Chen et al (2018), culture includes art, sports, cooking, music, dance, architecture, history, and family. The expression of culture is different in various countries, and successful enculturation of expatriates includes four dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen et al (2018) noted the physical and spiritual stress during expatriation and proposed that individual handling methods should include planning solutions and re-evaluating problem-solving tools (Stilianos et al, 2017), while emotional handling should include stress release, avoiding efforts to escape from reality, and seeking social assistance. Jyoti and Kour (2015) indicated that an expatriate should be able to effectively navigate the cross-cultural environment, including through the maintenance of psychological health and well-being, as well as self-confidence and effective stress management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modern scientific works emphasize the trend towards an increase in students' ability to self-study, self-management, and self-assessment [7]. Research in this field is predominantly concentrated on the questions of equity and the social mobility of education seekers [8], positive relationship between virtual reality and satisfaction from learning, and situation-based education, oriented at the acquisition of the necessary skills, knowledge, or behavior due to the use of complex technologies [9]. Researchers note that the vector of influence in modern education is transferred from the teacher to the student, who is supposed to design a personal learning trajectory with the teacher's help [10].…”
Section: Literature Reviewmentioning
confidence: 99%